Новые данные по морфологии и систематике личинок горбаток (Coleoptera, Mordellidae) фауны Дальнего Востока СССР - Мамаев, Б.М.; Односум, В.К. (Вестник зоологии, 1984)
Larvae of Tomoxia nipponica Kono, T. scutellata Kono, Tolidopalpus galloisi Kono and Yakuhananomia yakui Kono are for the first time described with special reference to the most important diagnostic characters: head capsule chaetotaxy, antennal structure, prothoracal tergite shape, stigmae, structure and armature of 9th abdominal segment.